On an asymptotic expansion of independent randomly distributed multidimensional random variables sum density - Saulis, L. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. И. Саулис. Асимптотическое разложение для плотности распределения сумм независимых неодинакого распределенных многомерных случайных величин L. Saulis. Nepriklausomų nevienodai pasiskirsčiusių daugiamačių atsitiktinių dydžių sumos tankio asimptotinis dėstinys